(untitled) (Research, Society and Development, 2022)
Higher education is a sui generis organization as it demands teaching, research and extension in constant feedback from its support system to the internal and external communities and their different agents: professors, students, managers, the scientific world and the community. And, if the enormous challenge were not enough, it must also exceed the specific nature of the teaching/learning process for a total management of didactic-pedagogical knowledge and its tacit and explicit conversions. The present study aims to reflect on this education in its articulations in the teaching, research and extension process, and its relations in the sense of an appropriate management of didactic-pedagogical knowledge. It is an essay with considerations on the management of didactic-pedagogical knowledge, starting from the characteristic model "wanting-to-know", to "know-how" and "can-do" - more prosperous to the generation of knowledge in an academic environment. In order to achieve this performance, the script follows: reflection on how the management of explicit didactic-pedagogical knowledge occurs in higher education, and the conversion of tacit didactic-pedagogical knowledge into explicit and vice-versa. This itinerary, structured in a theoretical framework that describes the management of knowledge involving the typology of tacit-explicit knowledge; the knowledge conception process – socialization (shared knowledge), externalization (conceptual knowledge), combination (systemic knowledge) and internalization (operational knowledge); didactic-pedagogical knowledge and, finally, the management of didactic-pedagogical knowledge. It is concluded that there is a need to potentiate in-service pedagogical training programs on an ongoing basis, as a way of fostering new concepts and experiences, training teachers and excellence in the teaching process.